Tradisi Reresik Sendang Masyarakat Wonosoco dalam Perspektif Ekoteologi Islam - Soraya, Ahna (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2019)
This study aims to determine the perspective of Islamic eco-theology in the Reresik Sendang tradition in Wonosoco Village. How the people of Wonosoco Village carry out, interpret, and how the Reresik Sendang tradition is seen from the perspective of Islamic eco-theology. This research uses a type of field research using a qualitative descriptive approach. Data collection techniques obtained through the results of observations, interviews, and documentation. The findings from this study indicate several important points: First, the tradition of Reresik Sendang is a form of effort by the people of Wonosoco Village in preserving the natural environment based on Islamic teachings. Secondly, in the implementation of the Reresik Sendang tradition, there are still rituals which are Hindu-Buddhist teachings. The community interpreted that the Sendang Reresik tradition is a form of gratitude to God Almighty, as well as a form of respect for the ancestors. Third, viewed from the perspective of Islamic eco-theology in the Reresik Sendang tradition in Wonosoco Village, there is a meeting point in it, which sees nature as a